2021
DOI: 10.1016/j.jvir.2020.11.018
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Global Registry of Paclitaxel Drug-Coated Balloon in Dysfunctional Arteriovenous Fistulae and Grafts: 6-Month Results

Abstract: To assess the safety and clinical benefit of the Lutonix drug-coated balloon (DCB) catheter for the treatment of dysfunctional arteriovenous fistulae (AVF) and grafts (AVG) in a heterogenous real-world population.Materials and Methods: This multicenter, prospective study enrolled 320 subjects from 12 countries in 25 sites across Europe and Asia. A total of 392 lesions were treated with the Lutonix 035 DCB catheter. Lesions were de novo and restenotic, located in every part of the circuit from the cannulation z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The primary role of the balloon platform is satisfactory drug delivery; therefore, vessel preparation before the application of a DCB and prolonged inflation time of DCB are important events for a successful outcome [9]. A recently published report confirmed that the procedural details had a significant role in target lesion primary patency (TLPP); pre-dilation before DCB angioplasty (77% with pre-dilation vs. 48.6% without pre-dilation, p = 0.0005) or DCB dilation for ≥120 s (p = 0.007) significantly improved TLPP in a subgroup analysis [10]. The use of a lipophilic excipient results in homogenous transfer of the drugs onto the vessel wall.…”
Section: Overview Of Dcbsmentioning
confidence: 91%
See 1 more Smart Citation
“…The primary role of the balloon platform is satisfactory drug delivery; therefore, vessel preparation before the application of a DCB and prolonged inflation time of DCB are important events for a successful outcome [9]. A recently published report confirmed that the procedural details had a significant role in target lesion primary patency (TLPP); pre-dilation before DCB angioplasty (77% with pre-dilation vs. 48.6% without pre-dilation, p = 0.0005) or DCB dilation for ≥120 s (p = 0.007) significantly improved TLPP in a subgroup analysis [10]. The use of a lipophilic excipient results in homogenous transfer of the drugs onto the vessel wall.…”
Section: Overview Of Dcbsmentioning
confidence: 91%
“…Recently published results of a DCB trial of 392 treatment areas in 320 participants from Europe and Asia who underwent DCB angioplasty included data from the Lutonix AV Global Registry, which is a multicenter, single-arm real-world registry, and suggested that a DCB is a safe and effective treatment option [10]. The access circuit primary patency was 71% at 6 months, and TLPP for stenosis of AVFs was 78.1%.…”
Section: Effectiveness Of Dcbs In Preventing Restenosis Of Arteriovenous Access According To Randomized Controlled Trialsmentioning
confidence: 99%
“…The majority of evidence for the above has come from literature regarding DCB use in atherosclerotic arterial disease, however, the same principles likely hold true in the treatment of AV access stenosis (68)(69)(70). Results of a multi-center global registry of DCBs in AVFs and AVGs, published by Karnabatidis et al, demonstrated improved outcomes in target primary lesion patency at 6 months in those who underwent pre-dilation (77%) compared to those who did not (49%), with P=0.0005 (71).…”
Section: Lesion Preparation (Pre-dilation)mentioning
confidence: 99%
“…Additionally, there was improved patency when lesions were pre-dilated with "focal force" balloons or cutting balloons as compared to normal HPBs (90). The previously mentioned global registry reported by Karnabatidis et al enrolled 320 patients with either AVFs or AVGs treated with the Lutonix DCB, with overall TLPP of 74% at 6 months, and significantly improved patency in those in whom the DCB was dilated for >120 seconds and in those in whom pre-dilation was performed (71).…”
Section: Yin Et Al 2021; Aperto Balloon (83)mentioning
confidence: 99%
“…Multiple individual studies have shown patency and/or re-intervention benefits of DEB vs. conventional angioplasty (12)(13)(14)(92)(93)(94)(95). However, meta-analysis studies have yielded variable conclusions, and patency rates over six months still have much room for improvement (96)(97)(98)(99).…”
Section: Current Challenges In Treating Avf Stenosis: a Call For Mechanism-based Approachesmentioning
confidence: 99%